Outdoor learning based on discovery learning to increase motivation to learn English for students - Ameliya Tus Soleha; Ahmad Dani; Bharadiansyah Tri Suryanto (SCM PUBLISHING, 2026)
Purpose: This article aims to describe the implementation of Outdoor Learning through English Games and Speaking Practice based on Discovery Learning and to examine its effectiveness in increasing students’ motivation and activeness in learning English in a Islamic boarding school context. Method: This community service study employed a Participatory Action Learning System (PALS) approach involving 27 Grade IX R4 students at MTs Nurul Jadid. The activities were conducted in two outdoor learning sessions integrating English Games and Discovery Learning-based Speaking Practice. Data were collected through observation sheets, motivation questionnaires (pre-test and post-test), field notes, and brief interviews, and analyzed using quantitative and qualitative techniques. Findings: The results showed a significant improvement in students’ learning motivation and activeness. The average motivation score increased from 27–30 in the pre-test to 38–42 in the post-test. Students’ activeness also improved markedly, with active participation rising from 20% to 75% by the second meeting. The outdoor learning environment encouraged greater engagement, confidence, and enthusiasm in English learning activities. Conclusions: Discovery Learning-based outdoor learning activities with English games and speaking practice have been proven effective in increasing the motivation and activeness of ninth-grade R4 students in an Islamic boarding school. Contributions: This study demonstrates that Outdoor Learning integrated with English Games and Discovery Learning-based Speaking Practice can serve as an effective alternative strategy to enhance English learning motivation and activeness in an Islamic boarding school setting.